PENGETAHUAN, SIKAP, DAN STATUS GIZI ANAK SEKOLAH DI DISTRIK MUARA TAMI JAYAPURA - Dwi Astuti; Elisabet Bre Boli; Oktliana Pasangka (Universitas Fort De Kock, 2023)
Schoolchildren need enough nutrition to grow and develop according to their age. Schoolchildren in Indonesia still experience nutritional problems, such as macronutrient deficiencies, macronutrient excess, and micronutrient deficiencies. Good knowledge and attitudes are factors that support the realization of good nutrition practices. This study aims to look at the relationship between nutritional knowledge, attitudes, and nutritional status in schoolchildren. This is a cross-sectional research with 48 schoolchildren living in the Muara Tami District as research subjects. Data collected using a questionnaire and anthropometric measurements with a microtoise and digital scales. Data is processed with the SPSS 24 application using the Chi Square test. The test results showed that there was a relationship between the level of nutritional knowledge and attitudes towards nutrition with the nutritional status of school children, p-value 0.040 and 0.003 respectively. Knowledge of good nutrition will manifest good nutritional attitudes and practices, so that it can also help in improving good nutritional status as well. The need for proper nutrition education to increase school children's understanding of good nutrition.